2019
DOI: 10.3390/a12070139
|View full text |Cite
|
Sign up to set email alerts
|

A Credit Rating Model in a Fuzzy Inference System Environment

Abstract: One of the most important functions of an export credit agency (ECA) is to act as an intermediary between national governments and exporters. These organizations provide financing to reduce the political and commercial risks in international trade. The agents assess the buyers based on financial and non-financial indicators to determine whether it is advisable to grant them credit. Because many of these indicators are qualitative and inherently linguistically ambiguous, the agents must make decisions in uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…We use long-term borrowing to total borrowing as a structure ratio, equity to total assets ratio as a measure of solvency, and interest coverage ratio to measure coverage (Horrigan, 1966;Belkaoui, 1980;Ederington, 1985;Kamstra et al, 2001;Touray, 2004;Brabazon and O'Neil, 2006;Bellovary et al, 2007;Doumpos et al, 2015;Feki and Khoufi, 2015). Managerial characteristics represent management quality and are determined using ownership (measured using strategic ownership as an essential measure of control); reputation and experience, measured through the firm's age (See Yazdi et al, 2019;Czarnitzki and Kraft, 2007). Market characteristics are determined using size and valuation.…”
Section: Mf 493mentioning
confidence: 99%
See 1 more Smart Citation
“…We use long-term borrowing to total borrowing as a structure ratio, equity to total assets ratio as a measure of solvency, and interest coverage ratio to measure coverage (Horrigan, 1966;Belkaoui, 1980;Ederington, 1985;Kamstra et al, 2001;Touray, 2004;Brabazon and O'Neil, 2006;Bellovary et al, 2007;Doumpos et al, 2015;Feki and Khoufi, 2015). Managerial characteristics represent management quality and are determined using ownership (measured using strategic ownership as an essential measure of control); reputation and experience, measured through the firm's age (See Yazdi et al, 2019;Czarnitzki and Kraft, 2007). Market characteristics are determined using size and valuation.…”
Section: Mf 493mentioning
confidence: 99%
“…, 2015; Feki and Khoufi, 2015). Managerial characteristics represent management quality and are determined using ownership (measured using strategic ownership as an essential measure of control); reputation and experience, measured through the firm's age (See Yazdi et al. , 2019; Czarnitzki and Kraft, 2007).…”
Section: Data and Variable Descriptionmentioning
confidence: 99%
“…Consequently, the result showed that if the economic factors such as financial capacity, institutional capacity, and government are in a good mood, establishing the ECA is worthy. Yazdi et al(2019) [29] evaluated the performance of ECAs by Data Envelopment Analysis. They considered some inputs and outputs, and then based on those, these ECAs are evaluated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They considered some inputs and outputs, and then based on those, these ECAs are evaluated. The result demonstrated that among these ECAs, which one has efficiency and which one is inefficiency and how inefficiency ECAs can be changed to efficiency ECA.Karbassi Yazdi et al(2019) [29] suggested how can did credit risk in an uncertain environment. They did this model by Fuzzy Inference System (FIS).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation